The Effect of Tomate Juice On Trigliserida Levels Of Male White Rats Induced by Alloxan - FITRI HANDAJANI; Ibrahim Shihatta (Jurnal Ilmu Kesehatan dan Kesehatan, 2021)
Background: Tomato juice is believed to affect triglyceride levels in the blood because it contains lycopene. This study aims to determine the effect of tomato juice (Solanum lycopersicum) on blood triglyceride levels in the wistar strain of male Rattus norvegicus induced by alloxan. Methods: 24 were divided into 3 groups, (1) Group K (-) experimental animals without treatment, (2) Group K (+) experimental animals induced by alloxan 150 mg / kgBB, (3) Treatment group K (P) animals tried alloxan induced 150 mg / kg and got 1.75 ml / head of tomato juice. Results: There was a significant difference in mean triglyceride levels between groups K (-) and group K (+). This indicates that the induction of alloxan increases blood triglyceride levels. There were significant differences in the mean triglyceride levels between the K (+) and K (P) groups because tomato juice contained lycopene which could reduce triglyceride synthesis. Conclusions: Tomato juice (solanum lycopersicum) reduced wistar strain male Rattus novergicus triglyceride levels induced by alloxan.